2002
DOI: 10.1161/01.str.0000018009.83713.06
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Management of Spinal Dural Arteriovenous Fistulas

Abstract: Background and Purpose-In the early 1980s, it was demonstrated that surgical intradural division of the shunting vein to the medullary venous plexus cures a spinal dural arteriovenous fistula (DAVF) at low morbidity. There is, however, growing literature to support endovascular therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(105 citation statements)
references
References 18 publications
4
98
0
3
Order By: Relevance
“…10 Van Dijk et al, 37 reported a cure rate of only 25% (11/44 patients) after treatment with n-BCA embolization. After failed endovascular treatment, 31 patients were cured surgically; the 2 other patients refused surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Van Dijk et al, 37 reported a cure rate of only 25% (11/44 patients) after treatment with n-BCA embolization. After failed endovascular treatment, 31 patients were cured surgically; the 2 other patients refused surgery.…”
Section: Discussionmentioning
confidence: 99%
“…18 Bowel and bladder incontinence, erectile dysfunction, and urinary retention are seen late in the course of the disease process. 37 If the lesion is not treated, 50% of patients will become severely disabled and less than 10% will be able to walk independently after 3 years. 9 Favorable outcome depends on the progression of neurologic deficits at the time of diagnosis, which makes early diagnosis preferable.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its high sensibility, arteriography may be inconclus i v e . van Dijk et al 7 described two patients whose angiograms did not reveal a spinal AV fistula, although the patients had classic signs and symptoms, both clinically and on MRI. Criscuolo et al 6 described two patients with diagnosis of Foix-Alajouanine syndrome and a negative spinal art e r i o g r a p h y.…”
Section: Fig 1 A) Lombosacral T1-weighted With Gadolinium Mri Shows mentioning
confidence: 99%
“…In Group 1, symptoms develop slowly due to compression of the spinal cord and/or nerve roots by enlarged epidural venous pouches [1]. Treatment with endovascular occlusion and/or surgical disconnection of fistulas is required in patients with acute or rapidly progressive symptoms before the spinal cord damage becomes irreversible [2][3][4]. Benign fistulas are a developing indication for radiosurgery [5].…”
Section: Introductionmentioning
confidence: 99%
“…A cure rate of 25-77% for endovascular embolization using liquid adhesive materials for classic type d-AVs has been reported [2,7], and rapid improvements in symptoms are obtained after endovascular treatment [4]. However, it is difficult to treat d-AVFs supplied from multiple segmental arteries or the same pedicle to the anterior spinal artery using endovascular intervention.…”
Section: Introductionmentioning
confidence: 99%